Hubungan Citra Tubuh dengan Kecemasan pada Wanita Premenopause Di Desa Dham Ceukok Kecamatan Ingin Jaya Kabupaten Aceh Besar - Masthura Masthura; Khaira Rizki; Yuli Zuhkrina (NAJ Nursing Applied Journal, 2025)
Pre-menopause is a transitional phase before menopause characterized by physiological and psychological changes, including physical changes of body shape. These changes often trigger anxiety, especially when body image is perceived negatively. This study aims to determine the relationship between body image and anxiety levels in premenopausal women in Dham Ceukok Village, Ingin Jaya, Aceh Besar, 2025. This research used a quantitative method with a cross- sectional design. The population consisted of all women aged 40–50 years in Dham Ceukok Village, totaling 35 women, chosen using a total sampling technique. The instruments used were a body image questionnaire and an anxiety level questionnaire based on the Hamilton Anxiety Rating Scale (HARS). The data were analyzed using univariate and bivariate analysis with the Chi-square test. The study was conducted from May 5 to May 10, 2025. The results showed a significant relationship between body image and anxiety among premenopausal women in Dham Ceukok Village, with a value of 0.035 (p < 0.05). The results indicate that there is a relationship between body image and anxiety in premenopausal women in Dham Ceukok Village, Ingin Jaya, Aceh Besar District. It is recommended that health workers collaborate with the village to be more active in providing counseling or educational activities to maintain physical and mental health, especially for women in the premenopausal stage.